A study of irrigation and restorations of old coffe trees. I. Results from Botucatu experiment station - Tosello, Rino N.; Ferreira, João B.; Gadelha, Waldemar; Malta, Rui F.; Penteado, Alberto de Figueiredo; Barreto, Geraldo B. (Pesquisa Agropecuaria Brasileira, 2014)
This paper reports and discusses results referring to a field trial set up to study the possibilities of restoring the productivity of an old coffee plantation through irrigation and fertilization. The six year study which started in 1955, was conducted in a representative, well kept coffee grove of Bourbon variety, about 40 years old, located at the Experiment Station of Botucatu, State of São Paulo. Nine randomized blocks were used with a 2x2x2 factorial for the treatments within each block. The following treatments were compared; complete chemical fertilizer in two dosages, with and without manure, and with and without green manure as an annual intercrop. The irrigation treatment included, irrigation starting in April, starting in July, and no irrigation application was determined by soil moisture depletion, when about 70 mm were consumed from the 0-80 cm soil layer. The results showed substantial increase in production during the dry years, however the significance of this production was diminished by the biennial beating effect occurring in coffee plants. During wet years, that is, when the normal rainy period is lengthened due to unexpected early rains (after irrigation has already been carried out) production may often be reduced due to excessive leaching of needed fertilizer. Use of green manure as an annual intercrop was shown not to increase production; the same occurring with the use of organic manure in the dosage of about 20 kg every year per coffee tree (which in actuality is a group of tree to five trees originally planted in the same hole). When production of the treated plots was compared with the untreated border plot trees, an increase of about 14% was shown due to the effect of chemical fertilizer alone. However the present economical situation in Brazil does not favor the use of fertilizer on a profitable basis. Considering the success obtained in forming a new coffee plantation in places where there was before an old one, a practice which is growing in importance, it would riot be advisable to recommend the expenditure of trying to improve an old coffee plantation of the type reported.